From Neoliberalism to Pluralism: A Response to Mulheirn and Jacobs - Finlayson, Alan (The Political Quarterly, 2013)
This essay puts into context the debate between Michael Jacobs and Ian Mulheirn, exploring the theories and themes underpinning their arguments, published in issue 84 1 of the Political Quarterly. It discusses, firstly, the roots of Mulheirn's approach in European neoliberalism and, secondly, the roots of Jacobs' approach in a range of sources currently contending for authority over debates within the Labour party. These include themes drawn, broadly, from Polanyi, Keynes, Schumpeter and Schumacher. In a conclusion the article makes the case for a ‘pluralistic’ to the organisation of political and economic power in the UK.
Keywords: neoliberalism; pluralism; political economy; social market